Bleeding risk and prediction model to predict bleeding risk of tissue biopsy for definitive diagnosis in patients with suspected amyloidosis - Watsamon Uraiwan; Pirun Saelue (Annals of Medicine)
Introduction Bleeding from the affected organs is a common manifestation of amyloidosis. The risk for perioperative bleeding in patients with amyloidosis remains controversial. In this study, we aimed to compare the bleeding risk of tissue biopsies for a definitive diagnosis between patients with and without amyloidosis, identify risk factors, and generate a prediction model for bleeding risk in these patients.Methods We enrolled patients aged >15 years who had amyloidosis as part of their differential diagnosis before tissue biopsy. After obtaining histopathological reports, we randomly selected patients with and without amyloidosis at a ratio of 4:1.Results A total of 360 patients were enrolled before tissue biopsy. Bleeding complications were observed in 5.6% and 4.2% of patients with and without amyloidosis, respectively. Amyloidosis was not associated with an increased perioperative bleeding risk (adjusted odds ratio 1.19; 95% confidence interval 0.17–8.41, p = 0.859). Kidney biopsy was a significant risk factor for perioperative bleeding in tissue biopsies. A KiHPL model was generated to predict the bleeding risk. The area under the curve was 0.87, with a good calibration plot for this model.Conclusions Amyloidosis is not associated with an increased risk of bleeding in tissue biopsies. The KiHPL model can predict the bleeding risk of tissue biopsies for a definitive diagnosis in patients with suspected amyloidosis.